OPTIMIZATION OF THE SOFTWARE INFRASTRUCTURE - Milan, KLEMENT; Miroslav, JANU; KVAPIL, Ludek (Trends in education, 2008)
The article treats the role of a new item in the developpement of local computer networks. It describes possible modes of optimization of the hardware and software infrastructures of a local computer network based on Microsoft technology.
Keywords: network infrastructure; hardware; software; service provided by a computer network; ESX server; Microsoft